Artificial Intelligence, Computer Assisted Instruction in Basketball Training - Zhao, Y.; Xie, J. (International Journal of Information Studies, 2025)
With the progress of science and technology, computer information technology has been widely used in various fields in our country. Artificial intelligence computer assisted instruction plays a very important role in enriching the form and means of basketball training. The concepts of artificial intelligence computer aided teaching technology and its main function in the actual basketball training teaching were introduced in this paper. Meanwhile, the content of basketball training and the application of artificial intelligence in basketball training methods were also elaborated. Finally the research results of artificial intelligence computer assisted instruction in basketball training were analyzed by means of a questionnaire survey. The expected goal consists of two aspects. One is to have the basic understanding the current application of artificial intelligence computer assisted teaching technology in China’s basketball training. Another one is to find out the existing problems of the technology in basketball training. In this way, we can provide a favorable direction for the future development of the application of artificial intelligence computer assisted instruction as well as enhance the student’s enthusiasm for basketball knowledge.